Spatiotemporal signatures of response to atrial fibrillation ablation. (3rd October 2022) - Ganesan, P; Rogers, A J; Deb, B; Feng, R; Rodrigo, M; Ruiperez-Campillo, S; Tjong, F V; Bhatia, N; Clopton, P; Rappel, W J; Narayan, S M
Abstract: Background: Atrial fibrillation (AF) can have organized regions, in the form of consistent dominant frequency sites, focal or reentrant sites, but it is unclear how these overlap with or differ from focal atrial tachycardias (AT) or potential drivers. We set out to develop an intuitive method based on fundamental electrogram shape and timing to separate types of AF. Objective: To test the hypothesis that spatial regions of electrogram (EGM) in AF that show similar shapes over time based on cross-correlation analysis may separate patients with differing response to ablation. Methods: We recruited N=133 patients (63.8±12.1 Y, 32% women), (i) N=10 had AT, (ii) N=122 AF that was or was not terminated by ablation, and (iii) N=1 pacing. All patients had left atrial mapping by 64 pole baskets. We applied repetitive activity (REACT) mapping that correlates EGMs in contiguous 2x2 regions (Fig. 1A) over 4sec. To calibrate REACT, we introduced simulated variations in shape (gaussian noise) and timing (gaussian delay) to pacing EGMs and computed nomograph over 100 random trials (Fig. 1C). Results: Fig. 1B shows that REACT in a 71-year-old man with AT is more organized than in a 65 YO man with AF (100% vs 40% mapped field). Overall, REACT was higher in AT than AF (0.63±0.15 vs 0.36±0.22, p<0.001). There were 24 cases in which global REACT between AF and AT groups had the overlapping range of values, indicating organized "islands" in AF analogous to AT. From nomograph in Fig. 1C we identified that this overlap reflects 15 ms variation in cycle length and 20% variation in EGM shape (labelled "x" in Fig. 1C). Conclusion: Basic electrogram properties in AF of similar shapes in spatial areas over time can separate response to ablation and may represent "islands" of AT. Future studies should investigate the mechanisms for such islands and whether they may be targeted for therapy. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): US National Institutes of Health